Aid works in sound policy environments - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Assessing Aid: What Works, What Doesn't, and Why, D Dollar and L Pritchett. A World Bank Policy Research Report 1998. 160 pp. Published for The World Bank by Oxford University Press. Stock No. 61123 (ISBN 0-19-521123-5). US$30.00